Preoperative botolinum toxin A (BTA) and intraoperative fascial traction (IFT) in the management of complex abdominal wall hernias - Niebuhr, Henning; Wegner, Felix; Dag, Halil; Reinpold, Wolfgang; Woeste, Guido; Köckerling, Ferdinand (Hernia : the journal of hernias and abdominal wall surgery, 2024)
Introduction Preoperative botolinum toxin A (BTA) administration to the lateral abdominal wall has been widely used since its introduction for treating complex abdominal wall defects and loss of domain (LOD) hernias. Intraoperative fascial traction (IFT) is an established technique for complex abdominal wall hernias exceeding a width of 10 cm and has also shown auspicious results. We present our single center data including 143 consecutive cases combining both techniques from 2019 to 2023. Aim of the study was to develop an algorithm for a tailored approach for very large and complex ventral abdominal wall hernias. Methods Consecutive patients treated with preoperative BTA and IFT from August 2019 to December 2023 were identified in our prospectively maintained database and reviewed retrospectively. Metrics included intraoperative findings and short-term (30 days) postoperative outcomes. Results 143 patients were included in our retrospective analysis. The mean age was 58.9 years and 99% of all patients had an ASA Score of II or III with a mean body mass index of 32.4 kg/m 2 . The mean intraoperative reduction of fascia-to-fascia after BTA and IFT was 9.81 cm. 14 patients either had a lateral defect or a combination of a midline and lateral hernia. An additional uni- or bilateral transverse abdominis release (TAR) was necessary in 43 cases (30.1%). The overall surgical site occurrence rate (SSO) was 30.1% of which 13.8% were surgical site infections (SSI). Re-operation and SSO rates were significantly higher if an additional TAR was performed (both p = 0.001; α = 0.05). Conclusions IFT in combination with BTA is a transformative and clinically proven tool in the surgeons’ toolbox. It might be an easier, and less invasive alternative to other available techniques in many cases, but it should not be looked at as an ultimate stand-alone method to treat all complex W3 hernias.